Hubungan Efek Samping Suplemen Zat Besi (Fe) dengan Kepatuhan Ibu Hamil di Puskesmas Sumbersari Kabupaten Jember (The Association between Side Effects of Iron Supplementation and Medication Adherence among Pregnant Women in Sumbersari Health Center Jember Regency, East Java) - Irvina Anggita Baharini; Antonius Nugraha Widhi Pratama; Fransiska Maria Christianty (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Current knowledge shows that iron supplementation during pregnancy decreases risks of preterm birth and neonatal death. Adherence to iron supplements among pregnant women is very important as it has a large effect on mothers and fetuses. Side effects from iron tablets altogether with physical changes due to pregnancy may decrease patient adherence. Surveillance on medication adherence among pregnant women in Jember is limited. The purpose of this study was to determine the association between side effects and the adherence of pregnant mothers consuming iron tablets. This cross-sectional research used a questionnaire to assess mother's adherence in Puskesmas Sumbersari Jember Regency. A total of 90 pregnant women agreed to participate by giving their consent. The result showed that 58 respondents complained on nausea and vomiting (60.3 %), constipation (31.0 %), headache (17.2 %), diarrhea (10.3 %), and stomach pain (1.7 %). Side effects have negative association to the adherence in pregnant women (p=0.007). Keywords: side effects, iron supplementation, pregnancy